Canopy cover influence on macrofungal richness and sporocarp production in montado ecosystems - Santos-Silva, C.; Gonçalves, A.; Louro, R. (Agroforestry Systems, 2011)
In this study we aimed to ﬁnd out how macrofungi richness and sporocarp production varies in relation to both canopy cover and proximity of crown projection area, in order to discuss strategies and point out management actions that ensure macrofungal communities sustainability in montado ecosystems. The sporocarp survey was conducted once every two weeks, from October to February, between 2007 and 2009 in two representative sites of the most common (cork and holm oak) open montado ecosystems in southern Portugal. Results showed that canopy cover strongly shaped macrofungal communities composition and yield. Denser canopy cover enhanced mycorrhizal richness and reduced saprotrophic yield. Furthermore, mycorrhizal richness and yield increased with tree proximity. Finally some forest management strategies are suggested in order to enhance macrofungal richness and productivity, in montado ecosystems.
Keywords: Cork oak; crown influence; Holm oak; macrofungal communities; Mediterranean ecosystem; montado; Portugal

Epigeous macrofungi of the Parque de Natureza de Noudar in Alentejo (Portugal) - Louro, R.; Calado, M.; Pinto, B.; Santos-Silva, C. (Mycotaxon, 2009)
This inventory represents the first list of the epigeous macrofungi collected in Parque de Natureza de Noudar (Barrancos, Alentejo, Portugal). Throughout 3 years 162 taxa were registered, from which 8 are new species for Portugal and 77 for Alentejo. Some of them are considered rare species whereas others have been suggested to acquire a conservation status.
Keywords: fungi; Holm oak; iberian peninsula; Mediterranean ecosystem; sporocarps